Modern Challenges of Education and Psychology of Personality Formation - Kazibekova N. A., Musaeva E. S., Kiselev A. A., Kharlanov A. S., Kaipbekova S. V., Chechel' G. I., Tselishcheva Z. A., Loginova N. A., Nikitina I. A., Doroschuk E. S., Sokolova G. A., Barashkina S. B., Sitdikova F. B., Borisova I. V., Ereshchenko I. V., Ziuzia A. A., Vasileva I. S., Shvaikina N. S., Zarubina R. V., Pershonkova E. A., Khazykova T. S., Sudakov O. V., Sudakov D. V., Belov E. V., Gordeeva O. I., Khatuntsev A. V. (Modern Challenges of Education and Psychology of Personality Formation, 2022)
nowadays federal state educational standards (FSES) are aimed at one of the main trends in education – individualization. In modern pedagogical theory, individualization in the educational process is aimed at developing the potential of students, taking into account their individual characteristics and using various forms and methods of educational activities that improve the personal and interpersonal qualities of students. In addition, the new realities of life force a person to engage in his education throughout his life. Based on this, it is necessary to pay attention to a new approach that can make the educational system more efficient, the «flipped classroom», aimed at the ability to learn. The relevance of this work lies in the fact that the «flipped classroom» technology is actively spreading in teaching methods and needs to be improved. The theoretical significance of this study lies in the systematization of the material on the «flipped class» technology, the description of its essence, the study of the features and the search for differences between this technology and the traditional methodology.
Keywords: информационные технологии; электронные образовательные ресурсы; electronic educational resource; information technologies; смешанное обучение; перевёрнутый класс; мониторинг учебного процесса; mixed learning; flipped classroom; monitoring of educational process